PVT1 dependence in cancer with MYC copy-number increase - Tseng, Yuen-Yi (Nature, 2014)
‘Gain’ of supernumerary copies of the 8q24.21 chromosomal region has been shown to be common in many human cancers(1–13) and is associated with poor prognosis(7,10,14). The well-characterized myelocytomatosis (MYC) oncogene resides in the 8q24.21 region and is consistently co-gained with an adjacent ‘gene desert’ of approximately 2 megabases that contains the long non-coding RNA gene PVT1, the CCDC26 gene candidate and the GSDMC gene. Whether low copy-number gain of one or more of these genes drives neoplasia is not known. Here we use chromosome engineering in mice to show that a single extra copy of either the Myc gene or the region encompassing Pvt1, Ccdc26 and Gsdmc fails to advance cancer measurably, whereas a single supernumerary segment encompassing all four genes successfully promotes cancer. Gain of PVT1 long non-coding RNA expression was required for high MYC protein levels in 8q24-amplified human cancer cells. PVT1 RNA and MYC protein expression correlated in primary human tumours, and copy number of PVT1 was co-increased in more than 98% of MYC-copy-increase cancers. Ablation of PVT1 from MYC-driven colon cancer line HCT116 diminished its tumorigenic potency. As MYC protein has been refractory to small-molecule inhibition, the dependence of high MYC protein levels on PVT1 long non-coding RNA provides a much needed therapeutic target.